Involvement of deleted chromosome 5 in complex chromosomal aberrations in newly diagnosed myelodysplastic syndromes (MDS) is correlated with extremely adverse prognosis - Zemanova, Zuzana; Michalova, Kyra; Buryova, Halka; Brezinova, Jana; Kostylkova, Karla; Bystricka, Dagmar; Novakova, Milena; Sarova, Iveta; Izakova, Silvia; Lizcova, Libuse; Ransdorfova, Sarka; Krejcik, Zdenek; et al. (Leukemia research, 2014)
MDS with complex chromosomal aberrations (CCA) are characterized by short survival and a high rate of transformation to AML. A comprehensive genome-wide analysis of bone-marrow cells of 157 adults with newly diagnosed MDS and CCA revealed a large spectrum of nonrandom genomic changes related to the advanced stages of MDS. Chromosome shattering, probably resulting from chromothripsis, was found in 47% of patients. Deleted chromosome 5 was unstable and often involved in different types of cryptic unbalanced rearrangements. No true monosomy 5 was observed. Patients with CCA involving deleted chromosome 5 had an extremely poor prognosis (median overall survival, 2 months).
Keywords: Genome instability; chromozomální delece; Chromosomes, Human, Pair 5; Male; retrospektivní studie; lidské chromozomy, pár 5; Myelodysplastic syndromes; srovnávací genomová hybridizace; Myelodysplastic Syndromes; prognóza; Adult; karyotyp; dospělí; Aged; mužské pohlaví; senioři; Chromothripsis; myelodysplastické syndromy; senioři nad 80 let; lidé; ženské pohlaví; Humans; Comparative Genomic Hybridization; Aged, 80 and over; Deletion 5q; Prognosis; Retrospective Studies; Female; lidé středního věku; Chromosome Deletion; Complex chromosomal aberrations; Karyotype; Middle Aged